SMU School of Accountancy ranked first in the world by BYU Accounting Research Rankings (2021) - Singapore Management University (Institutional Knowledge at Singapore Management University, 2022)
The school takes top spot worldwide in three categories - Citation Rankings, Archival Research (All Topics) and Archival Research (Financial Accounting).